Optimal energy management of water networks under quality conditions - Colajanni, Gabriella; Sciacca, Daniele; Paone, Letizia (International transactions in operational research, 2026)
In the context of sustainability, which has become fundamental today, we aim to optimize (reduce) the energy consumption due to the use of pumps that bring water from all the different reservoirs to the nodes of the distribution network. The proposed model allows us, thanks to the use of smart meters and new 5G technologies, to determine the optimal strategies (i.e., the optimal flows of water pumped by each pump of the network), taking into account the different quality indices of each reservoir and guaranteeing the water quality conditions required by law. We formulate the nonlinear optimization problem as a game in which each reservoir manager acts in a noncooperative manner while satisfying some shared constraints. Hence, a variational formulation is also proposed for all the reservoirs simultaneously, with existence and uniqueness results. Finally, some simulations highlight how the optimization strategy is useful.